2010
DOI: 10.1002/mds.22797
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal eating in restless legs syndrome

Abstract: have to be congratulated for their hypothesis on PD pathogenesis. They suggest that the sequence of the brain changes in PD follows specific and repeatable patterns in all cases, as well as that a prion-like process underlies neurodegeneration. These ideas could explain several features of PD, such as the high prevalence of olfactory, autonomic, or sleep abnormalities. However, any pathogenic hypothesis should also explain:1. The variable rate of progression. 2. The heterogeneous presentation. 3. The persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Interestingly, among RLS patients with nocturnal smoking, SRED was common (83%), and both phenomena often began simultaneously [94]. It has been debated whether SRED in RLS may be caused by dopaminergics because these agents are known to trigger daytime impulsive behaviors such as gambling [95][96][97][98][99]. However, through the preponderance of evidence, it is suggested that dopamine agents are not the cause of SRED.…”
Section: Nocturnal Eating (Ne) Is Pervasive Among Patients With Restlessmentioning
confidence: 99%
“…Interestingly, among RLS patients with nocturnal smoking, SRED was common (83%), and both phenomena often began simultaneously [94]. It has been debated whether SRED in RLS may be caused by dopaminergics because these agents are known to trigger daytime impulsive behaviors such as gambling [95][96][97][98][99]. However, through the preponderance of evidence, it is suggested that dopamine agents are not the cause of SRED.…”
Section: Nocturnal Eating (Ne) Is Pervasive Among Patients With Restlessmentioning
confidence: 99%
“…13,15 It has been suggested that nocturnal eating in RLS patients may be caused by dopaminergic agents as these agents are known to trigger impulsive behaviors such as gambling. 6,7 Conversely, dopamine agents suppress feeding behavior in animal models. 32 This report, following up previous investigations, provides strong evidence that dopaminergic agents help treat, and are not the cause of NE.…”
Section: Ne/sred In Rls Is Relieved By and Not Caused By Dopaminergicmentioning
confidence: 99%
“…5 Conversely it has been suggested SRED in RLS may be due to anti-RLS dopaminergic agents. 6,7 Most investigations of nocturnal eating (NE; eating after an arousal from sleep, prior to terminal awakening) have focused bRIEF SUMMARY Current knowledge/Study Rationale: This study compared the prevalence of NE and SRED in RLS to INS, a disorder with similar sleep disruption to determine whether nocturnal feeding behavior in RLS is merely "killing time." We then prospectively determined therapeutic response with dopaminergic and sedative medications.…”
mentioning
confidence: 99%
“…Until now, the literature has not clearly discriminated BED from SRED in PD patients. Additionally, previous reports of nocturnal eating in PD patients with drug-related compulsive eating may have included unrecognized cases of SRED [16,19] .…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not enroll PD patients, and used small pramipexole doses (up to 0.36 mg/day) during a short (2 weeks) treatment period. Besides, a case control study comparing RLS and nocturnal eating showed that patients who received dopaminergic therapy for RLS presented a tendency to have a higher risk of developing SRED [10,19] .…”
Section: Discussionmentioning
confidence: 99%